أثر استراتيجية الجدول الذاتي (K.W.L) في التحصيل والاحتفاظ بالمعلومات لدى طلبة جامعة البلقاء التطبيقية في مادة الثقافة الإسلامية - الذنيبات، محمد عبدالرحمن محمد (الجامعة الأردنية - عمادة البحث العلمي, 2021)
This study aims at identifying the effect of the self-schedule strategy (K.W.L) on achievement and retention of information among students of Al-Balqa Applied University in the subject of Islamic culture. The researcher used the semi-experimental method and then intentionally selected two divisions of the Islamic culture subject divisions taught by the same teacher to represent the sample of the study. Division No. (4) which holds (40) male and female students and Division No. (5) which holds (40) male and female students. After carrying out the equivalence of the two groups, division number (4) was chosen randomly to represent the experimental group that has been taught using the (K.W.L) strategy, Division No. (5) represented the control group that has been taught in the ordinary way. The researcher prepared an achievement test to measure achievement and retention of information. The results showed a statistically significant difference at the level of significance (α ≤ 0.5) between the mean scores of the control and experimental groups in the achievement and retention test in favor of the experimental group.
هدفت هذه الدراسة إلى تعرف أثر استراتيجية الجدول الذاتي (K.W.L) في التحصيل والاحتفاظ بالمعلومات لدى طلبة جامعة البلقاء التطبيقية في مادة الثقافة الإسلامية، استخدم الباحث المنهج شبه التجريبي، جرى اختيار شعبتين من شعب مادة الثقافة الإسلامية بصورة قصدية عند المدرس نفسه لتكون عينة الدراسة، شعبة (4) وعدد طلابها (40) طالبا وطالبة، وشعبة (5) وعدد طلابها (40) طالبا وطالبة، وبعد التأكد من تكافؤ المجموعتين جرى بالطريقة العشوائية اختيار شعبة (4) لتمثل المجموعة التجريبية التي درست باستخدام استراتيجية (K.W.L) والشعبة (5) لتمثل المجموعة الضابطة التي درست بالطريقة الاعتيادية، أعد الباحث اختبارا تحصيليا لقياس التحصيل والاحتفاظ بالمعلومات، أظهرت النتائج وجود فروق ذات دلالة إحصائية عند مستوى الدلالة (0.05 ≥ α) بين متوسطي درجات المجموعتين الضابطة والتجريبية في اختبار التحصيل والاحتفاظ ولصالح المجموعة التجريبية.
Keywords: التعليم الجامعي -- تدريس الثقافة الإسلامية -- التحصيل الدراسي -- الاحتفاظ بالمعلومات -- استراتيجيات التدريس -- استراتيجية الجدول الذاتي -- جامعة البلقاء التطبيقية